Coptisine Alleviates Pristane-Induced Lupus-Like Disease and Associated Kidney and Cardiovascular Complications in Mice - Yan, Yu; Zhang, Zhihui; Chen, Yucai; Hou, Biyu; Liu, Kang; Qin, Hailin; Fang, Lianhua; Du, Guanhua (Frontiers in Pharmacology, 2020)
Systemic lupus erythaematosus (SLE) is a chronic multi-system autoimmune disease with a high prevalence of kidney and cardiovascular complications. Considering that Rho-associated coiled-coil-containing protein kinases (ROCKs) play important roles in SLE, inflammation and cardiovascular disease, we hypothesized that coptisine, which has been found to inhibit ROCKs, may have an effect on SLE. The effect of coptisine was assessed in female BALB/c mice intraperitoneally injected with 0.5 mL of pristane. Serum autoantibodies were tested every month, blood pressure was measured every 2 months, and serum inflammatory markers, spleen pathologic characteristics, renal injury and vascular function were observed at 6 months. The results showed that coptisine decreased the levels of serum autoantibodies and serum inflammatory markers in the SLE mice, improved the pathologic characteristics of the spleen, and simultaneously improved renal injury, decreased inflammatory responses in the kidneys, reduced blood pressure and improved vascular endothelial function. Western blot assays revealed that inhibiting the activation of the NF-κB and Rho/ROCK signalling pathways and downstream signalling molecules might be the potential mechanisms of the effects of coptisine. Our findings suggest that therapy with coptisine may be a strategy for preventing SLE and ameliorating associated kidney and cardiovascular complications.